Meningkatkan Semangat Belajar Peserta Didik Kelas III SD Negeri 25 Ampenan Pelajaran Pendidikan Pancasila - Mia, Hermiati; Farmasari, Santi; Oktafiah, Era (Mataram University, 2025)
This study aims to enhance the learning enthusiasm of third-grade students at SD Negeri 25 Ampenan in Pancasila Education through the implementation of digital and concrete learning media, as well as the Problem-Based Learning (PBL) and Project-Based Learning (PJBL) models. The research employed a Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, which consists of four stages: planning, action, observation, and reflection. The learning media used included digital applications such as Wordwall, Canva, and YouTube, as well as various concrete media relevant to the learning material. The results of the study showed a significant improvement in both students’ learning enthusiasm and learning outcomes after the implementation of these media and models. The average student score increased from 60 to 80, accompanied by greater participation and enthusiasm during the learning process. The application of PBL and PJBL effectively developed students’ critical thinking, collaboration, and problem-solving skills, while also fostering a sense of responsibility for their own learning process. In addition, the use of technology-based learning media had a positive impact on students’ digital literacy. Through the integration of digital tools in the classroom, students became more skilled at accessing, understanding, and utilizing information creatively and responsibly. This approach aligns with the demands of 21st-century learning, promoting digital competence alongside academic achievement. Thus, the combination of innovative learning media and interactive models such as PBL and PJBL proved effective in creating a more active, collaborative, and enjoyable learning atmosphere. The study concludes that this approach successfully enhances the quality of Pancasila Education while shaping students who are not only academically competent but also possess strong character and uphold Pancasila values.